SEKUEN ASAM AMINO ANTI WHITE SPOT SYNDROME VIRUS (WSSV) PADA UDANG WINDU (PENAEUS MONODON) - Supriatna, I -; Yustiati, A. -; Iskandar - (Direktorat Sumber Daya Akademik dan Perpustakaan, 2014)
This study aimed to determine the amino acid sequencehomology, functional domains, the model predictionof protein structure and characteristics of genesencoding anti WSSV in black tiger shrimp (Penaeusmonodon) originated from Indramayu District. Theresearch method was qualitative descriptive analysis bycomparing the results of PCR isolation of genes encodinganti WSSV with GenBank sequence data. The resultsshowed that the sequence gene encoding anti WSSV inblack tiger shrimp DNA originated Indramayu genesequences homologous with Penaeus monodon AV gene,complate cds (no. Accession DQ641258.1) and Penaeusmonodon PMAV (PmAV) mRNA, complete cds (no.Accession AY3202750.1). C -type lectin is a functionaldomain of the amino acid sequences of anti WSSVin black tiger shrimp. The structure of the proteinencoding anti WSSV (c -type lectin) is characterized bythe presence of a signal peptide, alpha helix clusters, betastrand and there are in three cells zones. C-type lectinindicated could help improved the resistance of blacktiger shrimp from Indramayu district against WSSVand the c -type lectin could be found in various typesof organisms to be developed as an immunostimulatorysubstance.Key words: Amino acid sequence, anti WSSV, c-typelectin, black tiger shrimp, immunostimulatory